(untitled) (Journal of Atomic and Molecular Sciences, 2019)
The anharmonic force fields and spectroscopic constants of electronic ground state (X^1A') of diazirinone (N_2CO) has been investigated employing the DFT (B3LYP, B3PW91, and B3P86) and MP2 methods with the cc-pVnZ (n = D, T, Q) basis sets. The calculated equilibrium geometries, ground state rotational constants, fundamental vibrational frequencies, and equilibrium quartic centrifugal distortion constants of N_2CO are in comparison with experimental or theoretical data. The B3LYP results well reproduce the equilibrium geometries and spectroscopic constants. The anharmonic constants, vibration–rotation interaction constants, equilibrium sextic centrifugal distortion constants, Coriolis coupling constants, cubic and quartic force constants of N_2CO are theoretically predicted. The results show that DFT methods can afford more reliable theoretical values than MP2 method.